High-strength low-shrinkage anti-crack mass concrete and preparation method thereof
By using modified calcium oxide-calcium sulfaluminate composite expansion agent and modified blend in large volume concrete, the crack problem caused by temperature changes in large volume concrete is solved, and the improvement of low shrinkage, high strength and crack resistance is achieved.
Patent Information
- Application Number
- CN202510037817.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-10
- Publication Date
- 2025-04-25
AI Technical Summary
Large-volume concrete is prone to cracks due to temperature changes during construction, affecting the durability and appearance quality of the structure.
A blend composed of modified calcium oxide-calcium sulfaluminate composite expansion agent, modified crosslinked dextran and modified urea-formaldehyde resin is used to reduce the heat of hydration and improve the expansion performance, and reduce the temperature stress and shrinkage phenomenon.
It significantly reduces the hydration heat of concrete, reduces temperature stress, avoids the formation of cracks, and improves the compressive strength, split tensile strength and crack resistance of concrete.
Smart Images

Figure BDA0005236038600000071 
Figure BDA0005236038600000081
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of building concrete, and relates to a high-strength, low-shrinkage, crack-resistant large-volume concrete and a preparation method thereof. Background Art
[0002] China's "Massive Concrete Construction Standard" GB50496-2018 stipulates: Large-volume concrete with a minimum geometric dimension of not less than 1m, or concrete that is expected to cause harmful cracks due to temperature changes and shrinkage caused by hydration of cementitious materials in the concrete, is called massive concrete.
[0003] Cracks in large concrete can be divided into three types according to their depth: through cracks, deep cracks and surface cracks. Through cracks develop from concrete surface cracks to deep cracks and eventually form through cracks. They cut off the cross section of the structure, which may destroy the integrity and stability of the structure, and its harmfulness is more serious; while deep cracks partially cut off the cross section of the structure, which is also harmful to a certain extent; surface cracks are generally less harmful, but affect the appearance quality. If they are not controlled, they are very dangerous and are likely to develop into larger cracks, causing harm to the main structure.
[0004] One of the main reasons for the formation of cracks in large-volume concrete is temperature. First of all, cement will continuously release heat during the hydration process, which will cause the temperature inside the concrete to rise. When the temperature difference between the inside and outside of the concrete exceeds a certain limit, temperature stress will be generated. When the temperature stress is greater than the constraint force inside and outside the concrete, concrete cracks will occur. The greater the amount of cement used, the greater the hydration heat in the concrete and the higher the internal temperature. The cement hydration heat is one of the important reasons for the cracks in large-volume concrete. In addition to the cracks caused by the temperature change caused by the cement hydration heat reaction inside the concrete, the temperature change of the external environment during construction affects the pouring temperature of the concrete, which will also cause cracks in large-volume concrete. During the construction of large-volume concrete, the outside temperature will affect the change of the pouring temperature of the concrete. When the outside temperature drops sharply, the temperature difference between the inner and outer layers of the concrete will increase, thereby increasing the temperature stress of the concrete and causing concrete cracks. Therefore, the change of the outside temperature is also one of the factors affecting concrete cracks. This kind of crack caused by temperature change, whose width is within the allowable limit, generally does not affect the strength of the structure, but it does affect the durability of the structure, so it must be taken seriously and controlled. Summary of the invention
[0005] The main purpose of the present invention is that the mass concrete prepared by the present invention can reduce the hydration heat and improve the crack resistance during the preparation process, thereby avoiding temperature cracks and deformation of the concrete. The obtained mass concrete has the properties of low shrinkage, high strength, crack resistance, etc.
[0006] The present invention adopts the following technical solutions to achieve the above purpose:
[0007] A high-strength, low-shrinkage, crack-resistant mass concrete, comprising the following components in parts by weight:
[0008] 280-300 parts of Portland cement, 50-60 parts of low-calcium fly ash, 45-55 parts of granulated blast furnace slag powder, 700-750 parts of sand, 130-150 parts of crushed stone with a particle size of 5-16mm, 60-70 parts of crushed stone with a particle size of 16-31.5mm, 10-15 parts of water reducer, 18-23 parts of expansion agent, 30-40 parts of admixture, and 160-180 parts of water.
[0009] Furthermore, the water reducer is a polycarboxylate water reducer.
[0010] Furthermore, the expansion agent is a modified calcium oxide-calcium sulphoaluminate composite expansion agent.
[0011] Furthermore, the admixture contains modified cross-linked dextran and modified urea-formaldehyde resin; the mass ratio of the modified cross-linked dextran to the modified urea-formaldehyde resin is 1:(0.5-1).
[0012] The present invention provides a method for preparing the modified calcium oxide-calcium sulphoaluminate composite expansion agent, which specifically comprises the following steps:
[0013] The calcium oxide-calcium sulphoaluminate composite expansion agent and highly substituted cross-linked carboxymethyl cellulose are mixed and micronized, and then added into the molten sodium alginate. After being stirred evenly, they are dried and crushed to obtain the modified calcium oxide-calcium sulphoaluminate composite expansion agent.
[0014] Furthermore, in the above-mentioned modified calcium oxide-calcium sulfoaluminate composite expansion agent preparation method, the mass ratio of calcium oxide-calcium sulfoaluminate composite expansion agent, highly substituted cross-linked carboxymethyl cellulose, and sodium alginate is 1:(0.3-0.4):(1.5-2).
[0015] The present invention provides a method for preparing the modified cross-linked glucan, which specifically comprises the following steps:
[0016] Add cross-linked dextran and 1,4-cyclohexanedicarboxylic acid to silica sol, stir until the cross-linked dextran is fully swollen, remove excess water, add polyethylene glycol, and stir under negative pressure to obtain modified cross-linked dextran.
[0017] Furthermore, in the above-mentioned modified cross-linked dextran preparation method, the mass ratio of cross-linked dextran, 1,4-cyclohexanedicarboxylic acid, silica sol, and polyethylene glycol is 1:(0.06-0.08):(1.5-1.8):(0.8-1).
[0018] The present invention provides a method for preparing the modified urea-formaldehyde resin, which specifically comprises the following steps:
[0019] The micronized corn cob is mixed with molybdenum disulfide, moistened with water and heated in an oxygen-free environment at 400-500°C for 30-40 minutes, cooled to a temperature, and then a sulfuric acid solution with a mass fraction of 70-80% is added, and the mixture is kept warm at 40-50°C for 20-30 minutes, and urea-formaldehyde resin is added and mixed to obtain the modified urea-formaldehyde resin.
[0020] Furthermore, in the above-mentioned modified urea-formaldehyde resin preparation method, the mass ratio of corn cob, molybdenum disulfide, sulfuric acid solution and urea-formaldehyde resin is 1:(0.3-0.5):(0.1-0.15):(10-12).
[0021] The present invention provides a method for preparing the high-strength, low-shrinkage, crack-resistant large-volume concrete, which specifically comprises the following steps:
[0022] Add water to silicate cement, low-calcium fly ash, granulated blast furnace slag powder, sand, 130-150 parts of crushed stone with a particle size of 5-16mm, and crushed stone with a particle size of 16-31.5mm, and stir, then add water reducer, expansion agent, and admixture, mix well, and you can get high-strength, low-shrinkage, crack-resistant large-volume concrete.
[0023] The present invention has the following beneficial effects:
[0024] The invention improves the expansion performance of a conventional calcium oxide-calcium sulfoaluminate composite expansion agent and reduces its sensitivity to temperature. When preparing concrete, the temperature is slightly higher, the volume expands, and cement gaps are fully filled. When the temperature changes, the overall shape of the expansion agent does not change significantly, and the volume can be effectively maintained without shrinking, thereby avoiding cracks caused by shrinkage. The concrete of the invention adds an admixture composed of modified cross-linked dextran and modified urea-formaldehyde resin. The addition of the admixture can effectively reduce the hydration heat generated when preparing concrete, reduce the temperature stress generated inside, and avoid cracks caused by excessive hydration heat. DETAILED DESCRIPTION
[0025] The present invention is further explained below in conjunction with specific examples. It should be understood that these examples are only used to illustrate the present invention and are not used to limit the scope of the present invention. After reading the present invention, various equivalent modifications to the present invention by those skilled in the art all fall within the scope of protection of the claims of this application.
[0026] Example 1
[0027] Preparation of modified calcium oxide-calcium sulphoaluminate composite expansion agent:
[0028] 1 kg of commercially available calcium oxide-calcium sulfoaluminate composite expansion agent and 0.4 kg of highly substituted cross-linked carboxymethyl cellulose are mixed and micronized, and then added into 2 kg of molten sodium alginate. After stirring evenly, the mixture is dried and crushed to obtain a modified calcium oxide-calcium sulfoaluminate composite expansion agent.
[0029] Preparation of modified cross-linked dextran:
[0030] 1 kg of cross-linked dextran and 0.06 kg of 1,4-cyclohexanedicarboxylic acid were added to 1.8 kg of silica sol, and the mixture was stirred until the cross-linked dextran was fully swollen. Excess water was removed, and 1 kg of polyethylene glycol was added. The mixture was stirred under negative pressure to obtain modified cross-linked dextran.
[0031] Preparation of modified urea-formaldehyde resin:
[0032] Mix 1 kg of micronized corn cobs with 0.5 kg of molybdenum disulfide, moisten with water and heat in an oxygen-free environment at 500°C for 30 minutes. After cooling, add 0.1 kg of 80% sulfuric acid solution by mass, keep warm at 50°C for 20 minutes, add 10 kg of urea-formaldehyde resin and mix well to obtain modified urea-formaldehyde resin.
[0033] Preparation of high-strength, low-shrinkage, crack-resistant mass concrete:
[0034] Add 160kg of water to 280kg of Portland cement, 60kg of low-calcium fly ash, 45kg of granulated blast furnace slag powder, 750kg of sand, 130kg of crushed stone with a particle size of 5-16mm, and 70kg of crushed stone with a particle size of 16-31.5mm, and stir. Then add 15kg of polycarboxylic acid water reducer, 18kg of modified calcium oxide-calcium sulfoaluminate composite expansive agent, and 40kg of admixture (including 20kg of modified cross-linked dextran and 20kg of modified urea-formaldehyde resin), mix well, and you can get high-strength, low-shrinkage, and crack-resistant large-volume concrete.
[0035] Example 2
[0036] Preparation of modified calcium oxide-calcium sulphoaluminate composite expansion agent:
[0037] 1 kg of commercially available calcium oxide-calcium sulfoaluminate composite expansion agent and 0.3 kg of highly substituted cross-linked carboxymethyl cellulose were mixed and micronized, and added into 1.5 kg of molten sodium alginate. After stirring evenly, the mixture was dried and crushed to obtain a modified calcium oxide-calcium sulfoaluminate composite expansion agent.
[0038] Preparation of modified cross-linked dextran:
[0039] 1 kg of cross-linked dextran and 0.08 kg of 1,4-cyclohexanedicarboxylic acid were added to 1.5 kg of silica sol, and the mixture was stirred until the cross-linked dextran was fully swollen. Excess water was removed, and 0.8 kg of polyethylene glycol was added, and the mixture was stirred under negative pressure to obtain modified cross-linked dextran.
[0040] Preparation of modified urea-formaldehyde resin:
[0041] Mix 1 kg of micronized corn cobs with 0.3 kg of molybdenum disulfide, moisten with water and heat in an oxygen-free environment at 400°C for 40 minutes. After cooling, add 0.15 kg of 70% sulfuric acid solution by mass, keep warm at 40°C for 30 minutes, add 12 kg of urea-formaldehyde resin and mix well to obtain modified urea-formaldehyde resin.
[0042] Preparation of high-strength, low-shrinkage, crack-resistant mass concrete:
[0043] Add 180kg of water to 300kg of Portland cement, 50kg of low-calcium fly ash, 55kg of granulated blast furnace slag powder, 700kg of sand, 150kg of crushed stone with a particle size of 5-16mm, and 60kg of crushed stone with a particle size of 16-31.5mm, and stir. Then add 10kg of polycarboxylic acid water reducer, 23kg of modified calcium oxide-calcium sulfoaluminate composite expansion agent, and 30kg of admixture (including 20kg of modified cross-linked dextran and 10kg of modified urea-formaldehyde resin), mix well, and you can get high-strength, low-shrinkage, crack-resistant large-volume concrete.
[0044] Example 3
[0045] Preparation of modified calcium oxide-calcium sulphoaluminate composite expansion agent:
[0046] 1 kg of commercially available calcium oxide-calcium sulphoaluminate composite expansion agent and 0.35 kg of highly substituted cross-linked carboxymethyl cellulose were mixed and micronized, and added into 1.8 kg of molten sodium alginate. After stirring evenly, the mixture was dried and crushed to obtain a modified calcium oxide-calcium sulphoaluminate composite expansion agent.
[0047] Preparation of modified cross-linked dextran:
[0048] 1 kg of cross-linked dextran and 0.07 kg of 1,4-cyclohexanedicarboxylic acid were added to 1.7 kg of silica sol, and the mixture was stirred until the cross-linked dextran was fully swollen. Excess water was removed, and 0.9 kg of polyethylene glycol was added, and the mixture was stirred under negative pressure to obtain modified cross-linked dextran.
[0049] Preparation of modified urea-formaldehyde resin:
[0050] Mix 1 kg of micronized corn cobs with 0.4 kg of molybdenum disulfide, moisten with water and heat in an oxygen-free environment at 400°C for 40 minutes. After cooling, add 0.13 kg of 80% sulfuric acid solution by mass, keep warm at 50°C for 20 minutes, add 11 kg of urea-formaldehyde resin and mix well to obtain modified urea-formaldehyde resin.
[0051] Preparation of high-strength, low-shrinkage, crack-resistant mass concrete:
[0052] Add 170kg of water to 290kg of Portland cement, 55kg of low-calcium fly ash, 50kg of granulated blast furnace slag powder, 730kg of sand, 140kg of crushed stone with a particle size of 5-16mm, and 60-70kg of crushed stone with a particle size of 16-31.5mm, and stir. Then add 13kg of polycarboxylic acid water reducer, 20kg of modified calcium oxide-calcium sulfoaluminate composite expansion agent, and 36kg of admixture (including 20kg of modified cross-linked dextran and 16kg of modified urea-formaldehyde resin), mix well, and you can get high-strength, low-shrinkage, crack-resistant large-volume concrete.
[0053] Comparative Example 1
[0054] Preparation of high-strength, low-shrinkage, crack-resistant mass concrete:
[0055] Add 170kg of water to 290kg of Portland cement, 55kg of low-calcium fly ash, 50kg of granulated blast furnace slag powder, 730kg of sand, 140kg of crushed stone with a particle size of 5-16mm, and 60-70kg of crushed stone with a particle size of 16-31.5mm, and stir. Then add 13kg of polycarboxylate water reducer and 20kg of commercially available calcium oxide-calcium sulphoaluminate composite expansion agent and mix well to obtain high-strength, low-shrinkage, crack-resistant large-volume concrete.
[0056] Comparative Example 2
[0057] Preparation of modified calcium oxide-calcium sulphoaluminate composite expansion agent:
[0058] 1 kg of commercially available calcium oxide-calcium sulphoaluminate composite expansion agent and 0.35 kg of highly substituted cross-linked carboxymethyl cellulose were mixed and micronized, and added into 1.8 kg of molten sodium alginate. After stirring evenly, the mixture was dried and crushed to obtain a modified calcium oxide-calcium sulphoaluminate composite expansion agent.
[0059] Preparation of high-strength, low-shrinkage, crack-resistant mass concrete:
[0060] Add 170kg of water to 290kg of Portland cement, 55kg of low-calcium fly ash, 50kg of granulated blast furnace slag powder, 730kg of sand, 140kg of crushed stone with a particle size of 5-16mm, and 60-70kg of crushed stone with a particle size of 16-31.5mm, and stir. Then add 13kg of polycarboxylate water reducer, 20kg of modified calcium oxide-calcium sulfoaluminate composite expansion agent, 10kg of silica sol, and 20kg of urea-formaldehyde resin and mix well to obtain high-strength, low-shrinkage, and crack-resistant large-volume concrete.
[0061] Comparative Example 3
[0062] Preparation of modified cross-linked dextran:
[0063] 1 kg of cross-linked dextran was added to 1.7 kg of silica sol, stirred under negative pressure, and excess water was removed to obtain modified cross-linked dextran.
[0064] Preparation of modified urea-formaldehyde resin:
[0065] 1 kg of micronized corn cobs was mixed with a 40% by mass calcium carbonate aqueous solution and then immersed in a negative pressure environment for 40 minutes, excess water was removed, and 11 kg of urea-formaldehyde resin was added and mixed to obtain a modified urea-formaldehyde resin.
[0066] Preparation of high-strength, low-shrinkage, crack-resistant mass concrete:
[0067] Add 170kg of water to 290kg of Portland cement, 55kg of low-calcium fly ash, 50kg of granulated blast furnace slag powder, 730kg of sand, 140kg of crushed stone with a particle size of 5-16mm, and 60-70kg of crushed stone with a particle size of 16-31.5mm, and stir. Then add 13kg of polycarboxylic acid water reducer, 20kg of commercially available calcium oxide-calcium sulfoaluminate composite expansion agent, and 36kg of admixture (including 20kg of modified cross-linked dextran and 16kg of modified urea-formaldehyde resin), mix well, and you can get high-strength, low-shrinkage, crack-resistant large-volume concrete.
[0068] Performance Testing
[0069] 1. According to the "Code for Construction of Large Volume Concrete" (GB50496-2009), the compressive strength and splitting tensile strength of the large volume concrete obtained in Example 1 to Example 3 and Comparative Example 1 to Comparative Example 3 were tested.
[0070] Table 1 Concrete compressive strength
[0071] Age / d 1 3 4 5 6 7 9 28 Example 1 Concrete 18.2 34.2 37.0 41.4 40.4 43.8 45.7 57.8 Example 2 Concrete 18.9 33.8 38.9 40.6 42.3 44.2 45.2 60.3 Example 3 Concrete 18.4 33.4 38.1 40.4 42.2 43.4 46.1 59.6 Comparative Example 1 Concrete 8.0 26.0 26.1 27.0 29.6 32.0 33.5 44.8 Comparative Example 2 Concrete 9.0 25.7 25.6 28.6 30.6 32.8 33.8 46.9 Comparative Example 3 Concrete 9.2 26.2 26.6 28.1 29.2 32.4 34.0 45.2
[0072] Table 2 Concrete splitting tensile strength
[0073] Age / d 1 3 4 5 6 7 9 28 Example 1 Concrete 0.85 2.99 2.95 2.91 3.28 3.21 3.68 4.32 Example 2 Concrete 0.81 2.81 2.94 3.21 3.22 3.26 3.74 4.40 Example 3 Concrete 1.01 2.86 3.27 3.32 3.17 3.50 3.84 4.45 Comparative Example 1 Concrete 0.15 2.15 2.28 2.72 2.95 2.79 3.01 3.65 Comparative Example 2 Concrete 0.14 2.24 2.21 2.51 2.71 2.81 2.97 3.63 Comparative Example 3 Concrete 0.14 2.30 2.41 2.39 2.79 3.00 3.01 3.72
[0074] From the results in Table 1 and Table 2, it can be seen that the compressive strength and splitting tensile strength of the concrete prepared by the present invention are significantly higher than those of the concrete prepared by other comparative examples, indicating that the addition of the modified expansive agent and admixture in the present invention can significantly enhance the compressive strength and splitting tensile strength of the concrete.
[0075] 2. According to the "Test Procedure for Hydraulic Concrete" (DLT5150-2017), the concrete prepared by Example 1 to Example 3 and Comparative Example 1 to Comparative Example 3 was subjected to a 7d adiabatic temperature rise test; according to the "Standard for Test Methods for Long-term Performance and Durability of Ordinary Concrete" (GBT50082-2009), the concrete prepared by Example 1 to Example 3 and Comparative Example 1 to Comparative Example 3 was subjected to a 28d autogenous shrinkage test.
[0076] Table 3 Concrete insulation temperature rise and autogenous shrinkage
[0077] 7d adiabatic temperature rise / ℃ <![CDATA[28d self-shrinkage rate / ×10 -5 > Example 1 Concrete 26.2 5.06 Example 2 Concrete 26.9 5.24 Example 3 Concrete 27.3 4.73 Comparative Example 1 Concrete 45.1 8.96 Comparative Example 2 Concrete 36.5 9.07 Comparative Example 3 Concrete 53.9 8.11
[0078] From the results in Table 3, it can be seen that the adiabatic temperature rise of the concrete prepared by the present invention is lower than 30°C, and the autogenous shrinkage rate is only 4.73-5.24×10 -5 It has the characteristics of low temperature rise and low shrinkage, and is significantly better than the concrete prepared in each comparative example.
[0079] 3. The concrete prepared in Examples 1 to 3 and Comparative Examples 1 to 3 were used to prepare test specimens, and the early cracking sensitivity of the test specimens was evaluated according to the following evaluation criteria.
[0080] Evaluation criteria:
[0081] (1) Only very fine cracks;
[0082] (2) The average crack area is less than 10 mm 2 ;
[0083] (3) The number of cracks per unit area is less than 10 trees / m 2 ;
[0084] (4) The total crack area per unit area is less than 100 mm 2 / m 2 .
[0085] According to the above four criteria, cracking sensitivity is divided into five levels.
[0086] (1) Level I: Meet the above 4 criteria;
[0087] (2) Level II: meets three of the above four criteria;
[0088] (3) Level III: meeting two of the above four criteria;
[0089] (4) Level IV: Meets one of the above four criteria
[0090] (5) Level V: None of the requirements are met.
[0091] Table 4 Concrete crack resistance
[0092]
[0093]
[0094] From the results in Table 4, it can be seen that the specimens prepared by the concrete of the present invention have better crack resistance, the crack width and crack area of the specimens are both lower, the number of cracks is smaller, and the overall crack resistance is better than the specimens prepared by the concrete of each comparative example.
Claims
1. A high-strength, low-shrinkage, crack-resistant mass concrete, characterized in that: In parts by weight, it contains the following ingredients: 280-300 parts of Portland cement, 50-60 parts of low-calcium fly ash, 45-55 parts of granulated blast furnace slag powder, 700-750 parts of sand, 130-150 parts of crushed stone with a particle size of 5-16mm, 60-70 parts of crushed stone with a particle size of 16-31.5mm, 10-15 parts of polycarboxylic acid water reducer, 18-23 parts of expansion agent, 30-40 parts of admixture, and 160-180 parts of water.
2. The mass concrete according to claim 1, characterized in that: The expansion agent is a modified calcium oxide-calcium sulphoaluminate composite expansion agent.
3. The mass concrete according to claim 2, characterized in that: The preparation method of the modified calcium oxide-calcium sulphoaluminate composite expansion agent is: The calcium oxide-calcium sulphoaluminate composite expansion agent and highly substituted cross-linked carboxymethyl cellulose are mixed and micronized, and then added into the molten sodium alginate. After being stirred evenly, they are dried and crushed to obtain the modified calcium oxide-calcium sulphoaluminate composite expansion agent.
4. The mass concrete according to claim 3, characterized in that: In the preparation method of the modified calcium oxide-calcium sulfoaluminate composite expansion agent, the mass ratio of the calcium oxide-calcium sulfoaluminate composite expansion agent, the highly substituted cross-linked carboxymethyl cellulose and the sodium alginate is 1:(0.3-0.4):(1.5-2).
5. The mass concrete according to claim 1, characterized in that: The admixture contains modified cross-linked dextran and modified urea-formaldehyde resin; the mass ratio of the modified cross-linked dextran to the modified urea-formaldehyde resin is 1:(0.5-1).
6. The mass concrete according to claim 5, characterized in that: The preparation method of the modified cross-linked glucan is: Add cross-linked dextran and 1,4-cyclohexanedicarboxylic acid to silica sol, stir until the cross-linked dextran is fully swollen, remove excess water, add polyethylene glycol, and stir under negative pressure to obtain modified cross-linked dextran.
7. The mass concrete according to claim 6, characterized in that: In the modified cross-linked dextran preparation method, the mass ratio of cross-linked dextran, 1,4-cyclohexanedicarboxylic acid, silica sol and polyethylene glycol is 1:(0.06-0.08):(1.5-1.8):(0.8-1).
8. The mass concrete according to claim 5, characterized in that: The preparation method of the modified urea-formaldehyde resin is: The micronized corn cob is mixed with molybdenum disulfide, moistened with water and heated in an oxygen-free environment at 400-500°C for 30-40 minutes, cooled to a temperature, and then a sulfuric acid solution with a mass fraction of 70-80% is added, and the mixture is kept warm at 40-50°C for 20-30 minutes, and urea-formaldehyde resin is added and mixed to obtain the modified urea-formaldehyde resin.
9. The mass concrete according to claim 8, characterized in that: In the modified urea-formaldehyde resin preparation method, the mass ratio of corn cob, molybdenum disulfide, sulfuric acid solution and urea-formaldehyde resin is 1:(0.3-0.5):(0.1-0.15):(10-12).
10. A method for preparing mass concrete according to any one of claims 1 to 9, characterized in that: The following steps are involved: Add water to silicate cement, low-calcium fly ash, granulated blast furnace slag powder, sand, 130-150 parts of crushed stone with a particle size of 5-16 mm, and crushed stone with a particle size of 16-31.5 mm, and stir, then add polycarboxylic acid water reducer, expansion agent, and admixture, mix well, and you can get high-strength, low-shrinkage, crack-resistant large-volume concrete.
Citation Information
Cited By
Large-volume high-strength concrete suitable for underground structure and preparation method of large-volume high-strength concrete
CN121044853A
Massive high-strength concrete suitable for underground structures and method for producing the same
CN121044853B